Correction: A folate-conjugated platinum porphyrin complex as a new cancer-targeting photosensitizer for photodynamic therapy. Issue 3 (20th December 2019) - Yang, Mengqian; Deng, Jingran; Guo, Ding; Zhang, Jie; Yang, Lixia; Wu, Fengshou
Abstract : Correction for 'A folate-conjugated platinum porphyrin complex as a new cancer-targeting photosensitizer for photodynamic therapy' by Mengqian Yang et al., Org. Biomol. Chem., 2019, 17, 5367–5374.